ABOUT KABARDINO-BALKARIAN STATE UNIVERSITY FROM THE FIRST-PERSON PERSPECTIVE - Yuriy K. Altudov (Высшее образование в России, 2017)
The article presents a brief outline of conditions of occurrence, the main stages of the history, current state and prospects ofthe development of Kabardino-Balkarian State University.